Estudo da remediação de solo contaminado com diesel ou cromo (VI) aplicando eletrocinética e barreira reativa permeável de cortiça - Andrade, Deborah Cordeiro de (2022)
Taking into account the environmental problem related to soil contamination by organic and inorganic compounds, which is caused by the improper disposal of effluents and waste or accidental spills from the textile, food, agricultural and oil industries, there is a great need for them to be technologies have been developed which can minimize the impact of this pollution. This is a serious environmental issue, due to the high negative impact of heavy metals contamination, such as hexavalent chromium, and organic compounds, such as diesel. One way to reduce this impact is to apply remediation technologies to the soil, which promote the removal of these contaminants in an effective, low-cost manner and which also does not lead to new environmental problems. Aiming to provide new data on soils remediation, which are contaminated with hexavalent chromium and diesel, separately, this thesis presents an application study of electrokinetic technology combined with reactive permeable barrier of cork granules. To increase the removal of pollutants, chelating agents and surfactants were added as electrolytes. For electrokinetic remediation in soil contaminated with hexavalent chromium, the barrier used was composed of virgin cork and the electrolytes were: distilled water, citric acid (1 M), sodium chloride (0.1 M) and tap water. Although citric acid and sodium chloride presents higher conductivity than distilled water, results showed a superior removal of total and hexavalent chromium in EK-PRBa / DW-DW test, in which distilled water was added in the electrode chambers and cork granules placed close to the anode (41.5% removal). In terms of reduction, more than 82% of Cr (VI) was reduced to Cr (III) only by contact with the soil, probably due to the high concentration of Fe2+ in the soil (> 6000 mg kg-1 ). This behavior was enhanced by the presence of citric acid, which further lowered the pH of the soil. The test in which the sodium chloride was both electrolytes showed the lowest removal rate, probably due to the decrease in the availability of its ions by the formation of salts and bases with cations present in the soil matrix. For remediation in soil contaminated with diesel, the barrier used was composed of black cork and the electrolytes applied were: tap water, sodium sulfate (0.05 M) and sodium dodecyl sulfate (3.46 M). Results showed that, although SDS and Na2SO4 presents more intensive effects on organic migration due to their affinity with oil and dissociate ions with greater conductive capacity, compared with tap water, the test in which this electrolyte was used promoted a better rate of diesel removal, reaching 85.3%. However, the application of SDS and Na2SO4 also promoted satisfactory results (72.4%).